Spark plasma sintering behavior of Ti-3Al-1Mo alloy. (2021) - Jeje, Samson Olaitan; Shongwe, Mxolisi Brendon; Rominiyi, Azeez Lawan; Babalola, Bukola Joseph; Olubambi, Peter Apata
Abstract: Titanium alloys with 3 wt% Al and 1 wt% Mo were prepared at different sintering temperatures (800 °C, 1000 °C, and 1100 °C) via spark plasma sintering technique. Sintering temperature effect on the compact's properties was investigated. The punch displacement curves show three distinct regions: particle rearrangement, solution precipitation, and thermal contraction. The microstructure shows the emergence of β Ti phase into the α Ti phase matrix as the sintering temperature increase. The relative density and microhardness values were found to increase with a decrease in porosity with the compact sintered at 1000 °C having the maximum values of 99.9% and 290 ± 21 HV respectively. An increment of 83.31% was obtained in the hardness value as the sintering temperature increased from 800 °C to 1000 °C.